2019
DOI: 10.1155/2019/6856327
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modulation on Tau Phosphorylation in Alzheimer’s Disease

Abstract: Tau hyperphosphorylation is a typical pathological change in Alzheimer’s disease (AD) and is involved in the early onset and progression of AD. Epigenetic modification refers to heritable alterations in gene expression that are not caused by direct changes in the DNA sequence of the gene. Epigenetic modifications, such as noncoding RNA regulation, DNA methylation, and histone modification, can directly or indirectly affect the regulation of tau phosphorylation, thereby participating in AD development and progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 142 publications
0
27
0
Order By: Relevance
“…Thus, this pathology results in early nonamnestic features such as dyscalculia and aphasia [ 61 ]. Copper and iron are core redox active transition metals that interact with Aβ to facilitate the electron transfer necessary for the generation of ROS and reactive nitrogen species (RNS) in a reaction that requires tyrosine 10 [ 76 ]. Hydrogen peroxide (H 2 O 2 ), one of the most prominent free radicals produced in AD brains due to oxidative stress, is an uncharged, stable, and freely diffusible ROS.…”
Section: The Mechanism Underlying Ad Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this pathology results in early nonamnestic features such as dyscalculia and aphasia [ 61 ]. Copper and iron are core redox active transition metals that interact with Aβ to facilitate the electron transfer necessary for the generation of ROS and reactive nitrogen species (RNS) in a reaction that requires tyrosine 10 [ 76 ]. Hydrogen peroxide (H 2 O 2 ), one of the most prominent free radicals produced in AD brains due to oxidative stress, is an uncharged, stable, and freely diffusible ROS.…”
Section: The Mechanism Underlying Ad Developmentmentioning
confidence: 99%
“…As a result, the synthesis, transport, release, and uptake of neurotransmitters gets disrupted. Such interactions promote neurotoxicity, aggravate tau and Aβ deposition, and ultimately lead to more cellular lesions and sporadic neurodegeneration [ 73 , 76 , 80 ]. Finally, progressive damage and death of neurons in several areas of the brain, expressly the hippocampus—an important region for learning and memory—represent the direct cause of clinical manifestations in AD [ 16 , 23 , 28 ].…”
Section: The Mechanism Underlying Ad Developmentmentioning
confidence: 99%
“…Low levels of 5hmC have been detected in several brain regions of late stages AD patients, such as in the neocortex, hippocampus, entorhinal cortex and cerebellum [346][347][348]. On the contrary, 5mC levels were increased in the hippocampus of aging mice, but reduced in APP/PS1 transgenic mice, as well as in the hippocampus, enthorhinal cortex and cerebellum of patients with AD [349].…”
Section: Impact Of Dietary Factors On Dna Methylationmentioning
confidence: 99%
“…In addition, it has been observed that dementia risk increases due to an increase in the SIRT1 level [381]. Regarding this, data associated with epigenetics of AD indicate that low doses of RSV reduce the expression of genes crucial for age-related diseases [348], in particular there is cumulative evidence that RSV activates SIRT1 [348], which leads decreased neuronal loss caused by chronic inflammation.…”
Section: Impact Of Dietary Factors On Histone Post-translational Modimentioning
confidence: 99%
See 1 more Smart Citation